Care for the critical patient undergoing point-of-care testing: integrative review - Débora Thais Siqueira Soares; Ana Paula Hermann; Maria Ribeiro Lacerda; Marineli Joaquim Méier; Nayla Tamara de Godoi Caceres; Juliana Zimmermann Lima
ABSTRACT Objective: to identify, based on the evidence, point-of-care testing in bedbound in critically ill patients. Method: integrative review, carried out through search in Pubmed, Virtual Health Library, Joanna Briggs Institute, The British Institute of Radiology, Brazilian Radiology, and Google Scholar databases. We used the PICO research strategy and selected articles published from 2013 onwards, which presented information about point-of-care testing. Results: the different interventions found in the analysis of the 23 selected articles allowed the thematic grouping of care related to safety in communication, patient identification, care with devices, and the prevention and control of infection, which can be used in point-of-care testing. Final considerations: The care described in the evidence provided support for validating a safe care protocol for critically ill patients undergoing imaging studies in bed.